Effects of slide board training on the lateral movement of college-aged football players - Petersen, Tianna (My University, 2000)
The purpose of this study was to determine if training on the slide board would enhance lateral motion in collegiate football players. Forty-one collegiate football players (mean age 20.1 years) completed either a 10-week weight training (WT) or weight training plus slide board (WTSB) program. The following pre- and posttests were administered: the lateral shuttle run (LSR), the lower extremity functional test (L.E.F.T.), the cone test, the box test, and the squat and bench press tests. Following the pretesting evaluation, subjects were randomized into a WT group (N = 17) and a WTSB group (N = 24)i based on their pretesting stxength and agility scores. Both groups underwent 10-weeks of weight training, however, the WTSB group added a 3day/week slide board training. Data were analyzed using a 2-way ANOVA with repeated measures. It was found that there were significant differences (p < .05) in the pre- and posttests within both groups for the squat and bench press, the LSR, L.E.F.T., and cone test performances, but differences between groups were not significant (p > .05). For the box test, there were different responses between groups from pre- to post testing. The WT had a significantly (p < .05) lower score on post testing than pretesting, and this decline in performance was significantly (p c .05) different from the responses of the WTSB group. In conclusion, it appeared that slide board training had no beneficial effect for collegiate football players.
Keywords: Reebok Slide Trainer (Exercise machine); Football - Training; Leg - Movements; Motor ability - Testing; Human mechanics